FIM Strategic Planning and SKT Workshop 2016 - Sorooshian, Shahryar; M., Waris; Senthil Kumar , T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (FIM-UMP, 2016)
This workshop was held between 11 – 13, March 2016 involving all the staff members in Port Dickson, Negeri Sembilan